PREPARATION OF ORPHANS TO INDEPENDENT LIVING IN THE FAMILY EDUCATIONAL ENVIRONMENT - Олена Кузьміна (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article is devoted to problem of orphans' training for independent life that is based on their personal and psychological characteristics and features of educational environment. The problem of abandonment as a social phenomenon is considered from the point of view of this phenomenon genesis research and the impact of institutions that can overcome this problem. Particular attention is paid to the impact-family education and to formation and personal development of orphans. The results of numerous studies indicate the primary importance of orphans' preparation for independent life only in family environment. The results of analysis of scientific and educational research on orphans' education in family conditions and recommendations for improving the effectiveness of activity due to planned and comprehensive social and educational support to foster families and family-type homes.